2012
DOI: 10.1093/protein/gzs003
|View full text |Cite
|
Sign up to set email alerts
|

A polymerizable GFP variant

Abstract: Flagellin has the ability to polymerize into long filaments under appropriate conditions. Our work aims at the construction of flagellin-based fusion proteins which possess polymerization ability and preserve the functional properties of the fusion partner as well. The hypervariable D3 domain of Salmonella flagellin, containing residues 190-283, is a good target for genetic engineering studies since it can be extensively modified or removed without disturbing the self-assembling ability. In this work a fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Previous studies have exploited the functional potential of the flagellin hypervariable region in vitro by replacing it with adhesive peptides 34 , 35 , fluorescence domains 36 , and glycosyl hydrolases 37 . However, prior to our discovery, only structural and adhesive functions for flagellins have been observed in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have exploited the functional potential of the flagellin hypervariable region in vitro by replacing it with adhesive peptides 34 , 35 , fluorescence domains 36 , and glycosyl hydrolases 37 . However, prior to our discovery, only structural and adhesive functions for flagellins have been observed in nature.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution structural studies revealed that the conserved terminal regions of flagellin are involved in subunit interactions in the filament core while the hypervariable central portion of the polypeptide chain, comprising residues 190–284, forms the D3 domain exposed on the filament surface 14 , 15 . We demonstrated that D3 is a structurally independent part of flagellin which has no direct role in filament formation 16 and it can be removed or replaced by foreign proteins without influencing polymerization ability 17 , 18 .…”
Section: Introductionmentioning
confidence: 95%
“…The prototype of flagellin-based polymerizable proteins has been successfully created by replacing the D3 domain of flagellin with the amino acid sequence of the xylanase A enzyme 17 . A polymerizable GFP variant has been also fabricated which exhibited intensive fluorescence and was capable of efficient filament formation 18 . In these cases, it was relatively simple to construct these fusions because the terminal regions of the inserted proteins were close to each other similarly to the two internal ends of flagellin generated upon removal of D3.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the PEG side-chains of the polymer form a comblike structure on the surface, leaving very limited ability to control the surface orientation and local environment of the RGD motifs. [19,20].…”
Section: Introductionmentioning
confidence: 99%